Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.33774/chemrxiv-2021-k3szw-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface NMR Using Quantum Sensors in Diamond

Abstract: Characterization of the molecular properties of surfaces under ambient or chemically reactive conditions is a fundamental scientific challenge. Nuclear magnetic resonance (NMR) spectroscopy would be the ideal technique, however it lacks the sen-sitivity to probe the small number of spins at interfaces. Here we use nitrogen vacancy (NV) centers in diamond as quantum sensors to optically detect NMR signals from chemically modified thin films. Aluminum oxide (Al2O3) layers, common supports in catalysis and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 12 publications
(5 reference statements)
0
23
0
Order By: Relevance
“…A recent study has expanded the aluminum oxide platform for surface NMR demonstrated by Liu et al 77 , including additional binding moieties such as biotin or azides by multiple follow-up functionalization of the Al2O3 support 100 . This approach enables the efficient coupling of biomolecules such as proteins or DNA to the aluminum oxide deposited on the diamond's surface and expands the prospect of surface NV-NMR for biomolecules or biochemistry 101 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study has expanded the aluminum oxide platform for surface NMR demonstrated by Liu et al 77 , including additional binding moieties such as biotin or azides by multiple follow-up functionalization of the Al2O3 support 100 . This approach enables the efficient coupling of biomolecules such as proteins or DNA to the aluminum oxide deposited on the diamond's surface and expands the prospect of surface NV-NMR for biomolecules or biochemistry 101 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, nanoscale NV-NMR employing shallow NV ensembles has shown its ability to measure NMR signals originating from surfaces and interfaces under chemical-relevant conditions expanding the toolbox of modern chemical analytics with widespread applications in catalysis, electrochemistry, and material research 77 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations